ANALISIS CITY BRANDING KOTA CIREBON SEBAGAI CULTURE-BASED TOURISM CITY - Ramadhanty, Ghina; Setianti, Yanti; Warta, Waska (DAS Institute, 2024)
City branding is a strategy to introduce a city through its advantages. Cirebon City has a city branding with the tagline